PEMANFATAN SAMPAH ORGANIK RUMAH TANGGA MENJADI PUPUK ORGANIK CAIR (POC) DAN ECO-ENZYM - Anwar, Guswarni; Yansen; Erniwati (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2025)
The organic kitchen waste that has been discarded can be processed into liquid organic fertilizer (POC), and those that are still in good condition and fresh can be processed into eco-enzymes with the addition of several other ingredients. This will assist the residents of Tebat Tenong Luar Village in obtaining alternative fertilizers and pesticides that are both environmentally and health-friendly on a budget. The activity aims to enhance the capacity of the Tebat Tenong Luar community, which serves as the driving force behind the village economy and the pioneers of the business of processing household organic waste into liquid organic fertilizer and eco-enzymes, and to provide information and knowledge to the Tebat Tenong Luar Village community regarding the processing of household organic waste into liquid organic fertilizer and eco-enzymes. In November 2024, activities were conducted in Tebat Tenong Luar Village, Bermani Ulu Raya District, Rejang Lebong Regency. Counseling and the practice of converting household organic waste into liquid organic fertilizer and eco-enzymes were employed to execute the activities. The activity was assessed by examining the final product results after three months. Keywords: liquid organic fertilizer, organic waste, coenzyme, tebat tenong luar